Culture wars in Brazil : the first Vargas Regime, 1930-1945 - Williams, Daryle, 1967- (E-Duke books scholarly collection., 2001)
Examines the role of the Brazilian government as it attempted to create a national culture during a fifteen-year period of authoritarian cultural management.